1992
DOI: 10.1080/15287399209531659
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of mercuric chloride and methylmercuric chloride in mice

Abstract: Future human exposure to inorganic mercury will probably lead to a few individuals occupationally exposed to high levels and much larger populations exposed to low or very low levels from dental fillings or from food items containing inorganic mercury; human exposure to methylmercury will be relatively low and depending on intake of marine food. Ideally, risk assessment is based on detailed knowledge of relations between external and internal dose, organ levels, and their relation to toxic symptoms. However, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Variation in toxicokinetics across strains may alter distribution, retention, or rates of metabolism from organic to inorganic mercury species. 40,41,43 Toxicokinetic explanations, however, predict lower thresholds for the induction of autoimmune disturbance following mercury administration to females of H-2-susceptible strains. 40 Here, we found no sexrelated effects on behavior at prepubertal time points in susceptible SJL mice, and only few postpubertally; in these instances, males were more significantly affected than females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in toxicokinetics across strains may alter distribution, retention, or rates of metabolism from organic to inorganic mercury species. 40,41,43 Toxicokinetic explanations, however, predict lower thresholds for the induction of autoimmune disturbance following mercury administration to females of H-2-susceptible strains. 40 Here, we found no sexrelated effects on behavior at prepubertal time points in susceptible SJL mice, and only few postpubertally; in these instances, males were more significantly affected than females.…”
Section: Discussionmentioning
confidence: 99%
“…Genes outside the H-2 region influence both the autoimmune sequelae associated with mercury 40 and its toxicokinetics. [40][41][42] We compared three mouse strains with differing H-2 and non-H-2 backgrounds; such modulatory genetic factors might have been obscured. Variation in toxicokinetics across strains may alter distribution, retention, or rates of metabolism from organic to inorganic mercury species.…”
Section: Discussionmentioning
confidence: 99%
“…Even in unpolluted areas, natural fish populations may have substantial body burdens of mercury (50-400 pg Hg/kg), of which 20-40% is inorganic (23). In areas tainted with mercury, fish bioaccumulate and biomagnify this metal largely through lower trophic feeding.…”
Section: Concentration and Time-dependent Effects Of Hgcl2 On Pbl Promentioning
confidence: 99%
“…Upon arrival mice were acclimated for at least one week prior to experimentation. Six week old mice were chosen on the basis of previous research that found this age to show sufficient sexual and neurological maturity for studying the effects of methylmercury exposure in mice (Doi and Kobayashi, 1982;Yasutake et al, 1990;Nielsen, 1992;Adachi et al, 1994). All procedures were approved by the Rutgers Institutional Animal Care and Use Committee.…”
Section: Animalsmentioning
confidence: 99%
“…Recently, Cheng et al (2006) have shown that IP injection of MeHg results in MeHg accumulation in the brain and significant induction of c-Fos protein levels that may potentially predict MeHg-induced neurotoxicity in the rat. Further it has been demonstrated that route of exposure (whether IP or oral) to MeHg does not alter the toxicokinetic whole-body retention or distribution of MeHg in mice (Nielsen, 1992). In light of this, the question of whether functionally active doses of MeHg can temporarily or even permanently alter neuronal function in the adult brain, such that responses to subsequent exposure to heterotypic neurogenic stimuli other than MeHg are altered, has not been widely explored.…”
Section: Introductionmentioning
confidence: 99%